A kinetic approach to describe the time evolution of red wine as a function of packaging conditions adopted: Influence of closure and storage position. (September 2017) - Venturi, Francesca; Sanmartin, Chiara; Taglieri, Isabella; Xiaoguo, Ying; Quartacci, Mike F.; Sgherri, Cristina; Andrich, Gianpaolo; Zinnai, Angela
Highlights: During bottle storage the closure provide the barrier against the atmosphere. Different storage positions deeply affected wine shelf-life during bottle aging. Wine degradation was faster when a natural cork without the capsule was utilised. Wine decay was significantly delayed when it was stored in the horizontal position. Abstract: During bottle storage the barrier against the external atmosphere is provided by the closure. In order to evaluate the influence of capsule and storage position in preserving the quality of the wine, this research project aimed to study the chemical and sensorial evolution of a red wine stored over a period of 12 months in glass bottles closed with natural cork stoppers with or without capsule and maintained in different storage position (horizontal vs vertical). The different storage conditions adopted deeply affected wine quality suggesting that their rational optimization could allow the maintenance of red wine quality during storage. In particular, wine degradation rate was higher when the wine was stored in glass bottles closed with a natural cork without the capsule, regardless of the position of storage. On the contrary wine decay was significantly delayed when it was stored in the horizontal position, independently from the closure system used.